(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose this study was to describe the scientific learning process for Biology lessons with material for measuring the density of liquids in 7th grade students of Yapa Middle School in Bogor Regency, West Java for the 2019/2020 academic year, secondly to find out whether there was an increase in learning outcomes in the use of discovery learning, the third was to find out whether there was an increase in learning outcomes in the use of Problem Base Learning learning. In this study, the experimental method of the type of One – Group Pretest-Posttest Design (One Group Pretest-Posttest) was used. It were processed using assumption, normality, homogeneity and t-test tests.The respondents were 45 at 7th grade students. The Scientific learning process at Yapa Middle School is quite good, especially Biology learning for 7th grade students. The teacher had invited students to think critically and learn to be independent and dare to be responsible for their own results. Students looked enthusiastic and eager to learn to find a solution and task.Discovery and Problem Base learning had their respective strengths and weaknesses. The results achieved in the use of Discovery Learning got an increase in value of 4.9624, while for Problem Base learning it was 1,243. So it could be said that discovery learning has a higher value than Problem base learning of 3.7194